The reflective practice model mapping the teaching practice principles in L2 speech production in an online ESL classroom - Galve, Ella Lee P ([Miagao, Iloilo] University of the Philippines Visayas, 2022)
Classroom management relies heavily on teacher's philosophical belief's and principles. However, due to the demands of teaching alone, and now the demands of the new learning modality, it issignificant to ask if they still have time to reflect if their teaching principles are tailored in students' learning. Thus, this descriptive qualitative study sought to map out teachers' practice principles in teaching speaking in an online class, through their reflective practices. Reflective practice is an integral part of the teaching-learning process. Through this, teachers can meditate on one's actions so as to involve in a process of continuous learning.In this study, Schon's (1983) Reflective Practice Model was used to map out ES teachers' reflective practices and principles in teaching speaking in an online class. The repsondents of the study were the five teachers who handle Oarl communication in Context for Senior High School learners, from pre-determined private schools in Iloilo. Semi-structured interview guide was utilized to gather data from the official participants through an online individual interview via Zoom Meeting. For the analysis pprocedure analysis was used. The general results of this study presents the following teaching principles of ESL teachers who teach speaking in an online ESL class: learners with low "affective filter" will learn speaking skills faster; the langauge input should be interesting for the learners; for novice learners, teachers should focus on their delivery rather than the form; input in the tsrget language should be provided sufficiently; the input should be understandable for the second language learners; learners should be given avenues to practice speaking in second language; the competency or objectives of the course should always be aligned with the activities; the assessment tools should be caefully planned; instruction needs to consider learners' individual differences; and motivational activities should be planned and well-thought of.
Special Problem (M.Ed.-English as a Second Language) -- [Miagao, Iloilo] : U.P. Visayas, July 2022.